Psychosocial determinant of creativity among secondary school students in Saki, Oyo State, Nigeria (2014)
Correlational research design was adopted to examine the extent to which psychosocial factors predicted creativity among secondary school students in Saki, Oyo State, Nigeria. Six hundred and seventy-seven respondents (female=312; male=365) whose age ranged from 12 to 22 with mean age of 5.17 drawn using multistage sampling technique participated in the study. Three research questions guided the study. Data collected using Animashaun (2007) was analyzed with Pearson Product Moment Correlation (PPMC) and Multiple Regression at 0.05 level of significance. Results show that emotional intelligence and parental involvement have positive relationship with creativity level (r= 0.194, P<.05) and (r= 0.172, P<.05) respectively, while peer group influence has negative correlation with creativity level. The three independent variables jointly accounted for 21.2% of the variance in the prediction of creativity. There is need for teachers, parents, counselling psychologists and other stakeholders to design activities and leaning experiences that will make new ideas are to be generated, developed and transformed into value.